Efekt sieciowy jako skutek rozwoju nowoczesnych technologii telekomunikacyjnych - Nadolny, Michał (Network effect as a consequence of developing new information technologies, 2005)
Some goods manifest a special kind of relationship between utility and number of adopters. Such a dependence is known in science as a network effect. This effect results increasing (decreasing as well in some conditions) utility of cellular telephony, FAX, Internet an many others, as the number of adopters grows. In fact the network effect derives from a concept of external effect, we draw differences and similarity between this two ideas. Article is a concise approach of network effect. Literature review, definitions and basic problems are discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 387-398